Delphi Study on Requirements for Master’s Degrees from the Perspective of Agricultural Communications Faculty - Quisto Settle; Audrey E. H. King; Lauri Baker (Journal of Applied Communications, 2025)
Agricultural communications is a young discipline and although undergraduate curriculum has been explored from multiple angles, master’s degrees have not been given the same level of attention. This study sought to fill this gap through exploring what should be included in an agricultural communications master’s degree from the perspective of current agricultural communications faculty members. A Delphi methodology was implored to address this purpose. Three rounds were used to build consensus around necessary skills, courses, and theories in a master’s degree program in agricultural communications. There were 30 respondents for round 1 (35.7%), 32 for round 2 (38.1%), and 27 for round 3 (32.1%). In the final round, 10 courses met the 80% threshold for consensus with agricultural communications theory being the only course all respondents thought should be required. Thirteen theories reached consensus with agenda setting, framing, and uses and gratification receiving 100% of support from responses in round 3. There were 40 skills that reached consensus in the final round with critical thinking, application of social science theories, and evaluation of information receiving full consensus. Granted a one-size-fits-all model does not make sense, results of the study, indicate a master’s curriculum should be based on communication theory, research methods, statistics, thesis/capstone, and an agricultural communications foundation course, with integration of research writing and data presentation within those courses.
Keywords: master’s degree requirements; consensus building; Delphi